Reconstruction of avulsion history of the Brahmaputra River: Rare example of a giant braided river course alteration through multi-channel multi-avulsion processes - MD. Raihanul Islam; Imran Khan; MD. Alifnur Salim; M.D. Musfequzzaman (Evolving Earth)
The avulsion scenario of the Brahmaputra has been a debated issue for quite a long time. This study aims to resolve this debate through reconstruction of the avulsion history of the Brahmaputra. We have addressed the processes, timeline and causes of the avulsion. Old maps and images from 1776 to 2023, evidence from contemporary literature and recent studies have been used in our study. We find that the process of creation of the Jamuna was started through capturing the flow of the Brahmaputra by the Jenni during the 1780s. Between 1780 and 1800 the Brahmaputra created two primary avulsion channels upstream and initiated the multi-avulsion process which was completed in the 1880s. The first avulsion channel conveyed the Brahmaputra flow into the Konaie directly and the second avulsion channel diverted the flow captured by the Jenni into the Konaie. Contemporarily, the flow-enriched Konaie switched its flow into the Jenni at downstream through an unnamed channel and the combined flow traveled through the bed of the Jenni before creating the confluence with the Ganges. In the whole process, the Konaie received, inflated and transported the dominant flow of the Brahmaputra and the Jenni became inferior over time. We have introduced a bend migration concept along with local sediment overload to focus on setting up a lower stability threshold of avulsion that led to the eruptive creation of the avulsion channels by a coupled switching mechanism imparted by high monsoonal discharges, avulsion of the Tista into the Brahmaputra and the high-magnitude floods.